2020
DOI: 10.29244/jtcs.7.01.28-36
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Drought-Inducible Dehydrin Promoter from Sugarcane (Saccharum officinarum L.) in Tobacco (Nicotiana tabacum L.)

Abstract: Dehydrin (DHN) is known to play an important role in plant response and adaptation to abiotic stresses (drought, high salinity, cold, heat, etc.). Previous research reported the increased expression of DHN in sugarcane stems exposed to drought stress for 15 days which may be controlled by its corresponding stress inducible promoter. The DHN promoter was succesfully isolated from sugarcane variety PSJT 941 (Pr-1DHNSo) and was cloned to pBI121 expression vector fused to a β-glucuronidase (GUS) reporter gene.  Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It showed that Pr-1DHNSo can be considered a constitutive promoter based on functional tests previously conducted (Minarsih et al, 2020). The study of DHN promoter also indicated that the Pr-1DHNSo promoter from sugarcane was expressed and induced by drought stress treatment in tobacco plants (Iskandar et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It showed that Pr-1DHNSo can be considered a constitutive promoter based on functional tests previously conducted (Minarsih et al, 2020). The study of DHN promoter also indicated that the Pr-1DHNSo promoter from sugarcane was expressed and induced by drought stress treatment in tobacco plants (Iskandar et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Prior research also showed that the activity of the sugarcane DHN promoter that controls the expression of the GUS promoter gene was greatly increased in drought-stressed transgenic tobacco plants, relative to well-watered tobacco plants (Iskandar et al, 2020).…”
Section: Transformation Of Pbi121-pr-1dhnso In Sugarcane Calli and It...mentioning
confidence: 99%
“…Basic fertilizers are given at the end of land preparation, while additional fertilizers are administered during plant growth. This additional fertilization is essential, specifically for plants with long growth phases, such as tomatoes (Maillard et al, 2015), tobacco (Iskandar et al, 2020), cauliflower (Sofian & Susila, 2018), and winged bean (Ishthifaiyyah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%